Mutiara Riyadhushshalihin / Imam Al - Nawawi ; penerjemah Ahmad Rafi Usmani ; penyunting Toto Edidarmo, Yadi Saeful Hidayat...Ed.2 - IMAM AL - NAWAWI; Ahmad Rafi Usmani; Toto Edidarmo; Yadi Saeful Hidayat (Mizan Pustaka, 2013)
903 hlm.; 24 cm